When more is less: Perceived barriers to collaborative learning by adult college students - Virginia G. Gonzalez; Barbara A. Mccaulay (Adult Education Research Conference, 1994)
Collaborative learning is postulated as a principle of effective facilitation of adult learning; little research regarding the effectiveness of this instructional strategy has been conducted. This paper presents findings gleaned from research conducted at four colleges with adult students, revealing common barriers to collaborative learning in need of examination and discussion.